Impacts of large-scale wave integration into a transmission-constrained grid. (April 2016) - Moazzen, Iman; Robertson, Bryson; Wild, Peter; Rowe, Andrew; Buckham, Bradley
Abstract: This paper presents a study of large-scale wave energy integration in which transmission constraints are considered. The Vancouver Island electrical grid is considered and is modelled using PLEXOS ® Integrated Energy Model software. The model incorporates the current transmission grid, the existing fleet of main generation stations and ten potential wave farm sites with a total generation capacity of 500 MW. The objectives are to investigate: 1) the potential contribution of wave power toward energy self-sufficiency, 2) the effects of transmission constraints on the viability of alternative wave farm sites, 3) the impacts of wave integration on the load profile. Findings suggest that wave energy integration can significantly reduce the energy dependency on neighbouring jurisdictions but the current grid infrastructure is not adequate to fully support 500 MW of wave power. In this regard, it is shown that potential wave power integration can significantly benefit from transmission expansion for particular pathways. Further, results show that wave integration leads to reductions in the share of energy supplied from other sources and that this reduction follows an annual pattern. This periodic trend is particularly important for a hydro-dominated (energy-limited) grid where water level in reservoirs is managed on monthly and yearly bases. Highlights: The paper presents a study of large-scale wave energy integration in which transmission constraints are considered. Wave energy integration can significantly reduce the energy dependency on neighbouring jurisdictions but the current grid infrastructure is not adequate to fully support 500 MW of wave power. Potential wave power integration can significantly benefit from transmission expansion for particular pathways. Wave integration leads to reductions in the share of energy supplied from other sources and this reduction follows an annual pattern.